Participatory accessibility: Creating audio description with blind and non-blind children - Di Giovanni, Elena (Journal of Audiovisual Translation, 2018)
This article focuses on participatory accessibility by providing a definition, several theoretical insights and practical examples. By reporting on an inclusive and participatory experience carried out with blind, partially sighted and non-blind children in the drafting, recording and using audio description (AD) for a live opera performance, the aim is to bring into the spotlight the potential benefits of making accessibility a collective, open enterprise where end-users and creators are one. The article also advocates for the participatory turn in media accessibility research and practice.